Heartbeat-related distension and displacement of the thoracic aorta in healthy volunteers - Rengier, Fabian; Weber, Tim; Henninger, Verena Anna; Böckler, Dittmar; Kauczor, Hans-Ulrich; Tengg-Kobligk, Hendrik von (European journal of radiology, 2012)
Purpose To test our hypothesis that distension and displacement in various segments of the healthy thoracic aorta are significant and can be predicted based on clinical characteristics. Materials and methods Sixty-one Caucasian volunteers without cardiovascular disease (49±16 years, range 19-82; 28 men, 33 women) divided into two age groups (A: <50, B: ≥50 years) underwent 1.5-T MRI. ECG-gated dynamic data sets were acquired at five locations perpendicular to the thoracic aorta. Aortic distension and Centre of Mass (CoM) displacement were determined as percentages of diastolic aortic diameter. A multiple linear regression model including age group, gender, location, mean arterial blood pressure, heart rate and body mass index was tested. Results Mean aortic distension averaged over all locations was 11.2±4.1% (age group A) and 6.7±3.3% (age group B), mean displacement 15.1±8.3% (A) and 11.0±6.2% (B). Systolic and diastolic aortic diameter and CoM position significantly differed at all locations (p<0.001). Distension and displacement could be predicted based on the regression model (p<0.001). Age group A and women exhibited significantly greater distension and displacement compared to age group B (p<0.001) and men (p<0.01), respectively. Distension increased, displacement decreased from proximal to distal. Conclusion Distension and translational displacement are significant at all levels of the thoracic aorta and can be predicted based on clinical characteristics.